(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article focuses on the examination of phraseological units (PUs) within the poetry of Vladimir Semenovich Vysotsky, a key figure in 20th-century Russian culture. The research investigates Vysotsky’s employment of phraseological units to craft poetry that is rich in emotional resonance and complexity, highlighting the distinct characteristics of his language and philosophical ideas. In Vysotsky’s poetry, phraseological units serve multiple purposes, including establishing atmosphere, defining characters, and amplifying irony or sarcasm. The study pays particular attention to the stylistic nuances of PUs and their contribution to the formation of the poet’s linguistic perspective. It further analyzes how Vysotsky adeptly manipulates phraseology to conjure vivid imagery, develop characters, and underscore the philosophical richness of his literary works.